Measuring 3D orientation of nanocrystals via polarized luminescence of rare-earth dopants - Kim, Jeongmo; Chacón, Reinaldo; Wang, Zijun; Larquet, Eric; Lahlil, Khalid; Leray, Aymeric; Colas-des-Francs, Gérard; Kim, Jongwook; Gacoin, Thierry (Nature communications, 2021)
Orientation of nanoscale objects can be measured by examining the polarized emission of optical probes. To retrieve a three-dimensional (3D) orientation, it has been essential to observe the probe (a dipole) along multiple viewing angles and scan with a rotating analyzer. However, this method requires a sophisticated optical setup and is subject to various external sources of error. Here, we present a fundamentally different approach employing coupled multiple emission dipoles that are inherent in lanthanide-doped phosphors. Simultaneous observation of different dipoles and comparison of their relative intensities allow to determine the 3D orientation from a single viewing angle. Moreover, the distinct natures of electric and magnetic dipoles originating in lanthanide luminescence enable an instant orientation analysis with a single-shot emission spectrum. We demonstrate a straightforward orientation analysis of Eu 3+ -doped NaYF 4 nanocrystals using a conventional fluorescence microscope. Direct imaging of the rod-shaped nanocrystals proved the high accuracy of the measurement. This methodology would provide insights into the mechanical behaviors of various nano- and biomolecular systems. Determining the orientation of nanoscale objects in three-dimensional space has typically required complicated optical setups. Here, the authors develop a simple method to retrieve the 3D orientation of luminescent, lanthanide-doped nanorods from a single-shot emission spectrum.